UNDERSTANDING AND ADVANCED TRAINING IN THE STUDY OF DESCRIPTIVE GEOMETRY - Yusubjonov Jonibek Farxod o’g’li (Journals Park Publishing, 2024)
Descriptive geometry is an important discipline in education, which helps to develop spatial thinking, visual perception and analytical skills. However, many students face difficulties in understanding and applying geometric principles and tools. In this article, we will look at various approaches and strategies that can be used to improve students' skills in the study of descriptive geometry.
Keywords: descriptive geometry, spatial thinking, visual perception, analytical skills, education, teaching methods, geometric principles, geometric tools, visualization, practical application, interactivity, modern technologies, computer graphics, virtual reality, teacher role, learning strategies, learning environment, geometric constructions, problem-solving, communication skills, collaboration, computer programs, automatic feedback, knowledge transfer, spatial relationships, two-dimensional images, three-dimensional objects.